Sanligation technique of orchidopexy-Our experience - Tiwari, Puneet; Joshi, Arvind; Chanchlani, Roshan (International Journal of Medical Research and Review, 2015)
Introduction: A debate still exists in literature whether to ligate the indirect hernia sac during herniotomy in orchiopexy and hernia surgery. The study is designed with the aim to evaluate whether the ligation of hernial sac during orchiopexy is necessary to prevent the development of postoperative hernia. Material and Methods: This prospective study was conducted in 25 children with an age range of 6 months to 15 years with a diagnosis of palpable undescended testis. Of the 25 cases, 19 were unilateral and 6 were bilateral cases. Of the 19 unilateral undescended testis, 8 were right-sided and 11were left-sided. All children underwent open orchiopexy without the ligation of the hernia sac. Results: Clinically and radiologically all the patients were followed up to a period of two years. No evidence of inguinal hernia was detected during the follow-up in any patient. Conclusion: According to this study ligation of hernial sac is not necessary during orchiopexy and leaving the remnant stump open is safe with no recurrence.